The Effect of Financial Ratio to Financial Distress Mediated by Profitability Ratio in PT Angkasa Pura II (Persero) - Handayani, Sri; Perwitasari, Erni Pratiwi; Hermawan, M Arif (JEJAK: Jurnal Ekonomi dan Kebijakan, 2021)
This study aims to analyse the effect of ratios of liquidity, solvency and activity on financial distress through ROE, ROA and ROI of PT Angkasa Pura II (Persero) as mediating variable. The decrease in the number of aircraft passengers due to restrictions on human movement due to Covid-19 pandemic affects airport revenues as indicated by deteriorating financial ratios and is thought to lead to financial distress. This study tries to detect the symptoms of financial distress in the state-owned enterprise engaged in airport services by looking at the direct and indirect effects of its financial ratios’ performance. By using secondary data from financial statements, this study tried to build a structural equation model to know the direct and indirect effect. The results of hypothesis testing indicated that the ratio of liquidity, solvency and activity had negative effects on the company’s ROE, ROA and ROI during the period 2001-2020, but only the activity ratio that had a significant effect. Meanwhile, the three ratios of liquidity, solvency and activity had direct negative but not significant on financial distress. Next, ROE, ROA, and ROI had a direct positive but not significant effect on the company’s financial distress during that period. The study concludes that there was no relationship between the three ratios to financial distress mediated by ROE, ROA and ROI of the company.